Escola da Terra in Minas Gerais: repercussions of continuing education in rural schools - Eliano de Souza Martins Freitas; Érica Fernanda Justino de Freitas; Maria de Fátima Almeida Martins; Nayara Cristine Carneiro do Carmo (Universidade Federal do Norte do Tocantins, 2022)
In this text, we present the repercussions of continuing education: Escola da Terra, developed by the Center for Studies and Research in Rural Education of the Faculty of Education of the Federal University of Minas Gerais, FAE-UFMG, in partnership with the State Department of Education of Minas Gerais Gerais, Municipal Education Departments and the Ministry of Education (MEC). The program has already carried out four offers between 2015 and 2021. Such training is based on principles of Rural Education: considering the school as a right, alternating training as a pedagogical condition and the protagonism of subjects as central. Anchored in these principles, the training process is built, considering the educational needs of the territories, articulating them to specific methodological procedures, questioning them about the school and its subjects, in order to understand them in order to act and transform the practice. The results of the training course of the four offers of the program in Minas Gerais were achieved, both at the individual quantitative level, with more than five hundred Pedagogical Action Plans (PAPs), and at the collective level, considering changes in schools in different municipalities in the State of Minas Gerais.